Psychosocial rehabilitation and chronic mental illness: international trends and South African issues. (December 2014) - Kramers-Olen, Anne L
Psychosocial rehabilitation of persons with chronic mental illness has received increasing research attention over the past three decades. It is now widely accepted that pharmacotherapy alone is insufficient to treat persons with chronic mental illness. Additionally, there has been a paradigm shift towards the integration of evidence-based rehabilitation models and recovery models, which focus on collaborative approaches to care. This article reviews research findings relating to psychosocial rehabilitation interventions and models, and considers the implementation of psychosocial rehabilitation policies and practices in the South African healthcare context. Challenges to implementation and recommendations are presented.